Analisis Fundamental, Dividen, dan Overconfidence: Sebuah Pengambilan Keputusan Investasi Saham - Subaida, Ida (Akuntansi & Ekonomika, 2023)
The COVID-19 pandemic that has occurred since December 2019 resulted the decline in stock prices, including the IDX. Fundamental Analysis (FA) describes the condition of a company in terms of profits generated by the company. Dividends (DVD) are profit sharing given to shareholders based on the number of shares owned. Overconfidence (OCF) can lead to individual behavioral tendencies to believe more in the knowledge they have. this research aims to analyze the effect of FA, DCD, and OCF on Investment Decisions Making (IDM). The results show that DVD and OVC affect IDM, but FA has no effect on IDM.